Exploring The Role of Management Accounting ‎InformationSystems in Enhancing Performance of Small ‎and MediumSized Enterprises (SMES) in East Africa: A ‎Critical Analysis - Yuanying, Li; JOHAR , DR. JALILA BINTI (International Journal of Accounting and Economics Studies, 2026)
This is an exploratory empirical study exploring the use of Management Accounting Information ‎Systems (MAIS) and its impact on the performance of SMEs in East Africa (Kenya, Uganda, ‎Tanzania, and Rwanda). While the use of digital accounting tools to improve financial ‎management is increasingly accepted, original empirical data on this topic remains limited in East ‎African countries.‎This paper uses raw data collected in 2025 from a survey of 51 SMEs and analyzes it using ‎descriptive statistics and topic coding. The results show that SMEs adopting MAIS primarily focus ‎on survival-related functions, with approximately 65% of adopters using budgeting functions to ‎adjust cash flow and 53% using budgeting functions to adjust costs. Growth-oriented SMEs are ‎more willing to use this technology, while major barriers to adoption include high costs, unstable ‎infrastructure, and insufficient digital literacy, particularly in rural areas.‎The findings reveal contingency benefits arising from firm maturity, complementing contingency ‎theory that emphasizes the survival needs of emerging economies. This article provides ‎policymakers and practitioners with actionable recommendations for modular, cost-effective ‎Management Accounting Information Systems (MAIS) to improve the performance of small and ‎medium-sized enterprises (SMEs)‎.
Keywords: Digital Transformation; East Africa; Financial Performance; MAIS; SMEs